PERSEPSI PENYULUH PERIKANAN TERHADAP KINERJA KELOMPOK PEMBUDIDAYA IKAN DI KECAMATAN LOA KULU KABUPATEN KUTAI KARTANEGARA - Noli Duma To`Biri; Helminuddin; Nurul Ovia Oktawati (2339-1324, 2021)
The purpose of this study was to determine the level of perception of fisheries instructors on the performance of fish cultivation groups in the villages of Panoragan, Sepakat, Jembayan and Sumber Sari Village in Lao Kulu District, Kutai Kartanegara District. The study was conducted for 9 months (January-September). The sampling method used in this study is a purposive sampling method with 5 respondents. Data were analyzed using descriptive qualitative methods . The results of the study of Fisheries Perception of the Performance of Fish Cultivators in the Loa Kulu sub District of Kutai Kartanegara District, the partial planning indicators are in the high category with a score of 8.8. Indicators of partial organizational ability are in the high category with a score of 9. Institutional access indicators partially are in the high category with a score of 9. Indicators of entrepreneurial ability are partially in the high category with a score of 9. Indicators of independence are partially in the high category with a score of 9.